(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2015)
The hydrochemistry and pollution status of tannery effluent as well as the Buriganga River were studied. The water quality parameters namely temperature, pH, salinity, TDS, EC, DO, COD, Cr, Cd, Ni, Cu and Zn of tannery effluent were 22.8-31.5 oC, 7.4-10.6, 3920-6280 mg/l, 4680-7220 mg/l, 7070-10810 ?s, 0.3-1.1 mg/l, 1020-3800 mg/l, 7.7656 mg/l, 0.0198 mg/l, 0.2070 mg/l, 0.0304 mg/l and 0.3021 mg/l, respectively whereas in water of the Buriganga River were 22.0-31.6 oC, 6.2-7.8, 69-642 mg/l, 97-871 mg/l, 146-1309 ?s, 1.1-4.1 mg/l, 140-800 mg/l, 0.0306-0.2163 mg/l, 0.0018-0.0162 mg/l, 0.0663-0.2486 mg/l, 0.0112-0.0238 mg/l and 0.0878-0.2948 mg/l, respectively. According to the statistical analysis Salinity, EC, TDS, COD, Cr, Cd, Cu and Zn show positive correlations with each other and negative correlations with Temp. and DO. Ecological risk factor shows that Cr is the highest risk metal for ecosystem. The hydrochemistry has been revealed that the water is not safe for aquatic lives. Bangladesh J. Sci. Ind. Res. 50(2), 123-134, 2015